From Stones to Pages and Back. Trans-media Translations in the Notre-Dame of Victor Hugo and Viollet-le-Duc - Ramazza , Elena (E|C, 2023)
The French restorer Eugène Viollet-le-Duc (1814-1879) acknowledged two natures into the architectonical artworks: the spiritual and the material one. With his restorations, he aimed to restore the spirit of the buildings, while the matter, which was kept in a subordinate position, could be modified or sacrificed. Such concept of spirit consisted roughly in considering a building as a subject capable of producing signification, and had one of its theoretical basis in the chapter “Ceci tuera cela” of Notre Dame de Paris (1836) by Victor Hugo. There, the author reflected on the death of the cathedrals by the action of the print, which had inherited its communicative power. Therefore, Hugo and Viollet-le-Duc detected a significative strength in the stones of the cathedrals and both of them translated it into words: the first in his literature, the second in scientific publications, such as his Dictionnaires. Finally, Viollet-le-Duc walked the reverse path getting back to stones: with his restorations he used the matter as a flexible mean and modified it in order to restore the original spirit of the monuments.